“Proceso de atención de enfermería aplicado a pacientes con colecistitis" - González Jima, Miryam Gabriela;Elisa Álava Mariscal (2018)
Acute cholecystitis is one of the main complications of vesicular lithiasis, it is characterized by the swelling of the vesicular wall, which can produce several complications in the patient's health such as gangrene, empyema and perforation of the gallbladder. it is derived in different complex diseases such as generalized peritonitis, perivesicular abscesses and fistulas, the medical-surgical treatment is laparoscopic cholecystectomy accompanied by antibiotic therapy. Worldwide this pathology afflicts millions of people, every year new cases increase, women are more prone than men, since their risk is related to pregnancy, the use of contraceptive methods and hormone therapy in menopause. In men, the conditioning factors are weight, excessive consumption of tobacco and metabolic disorders among others. The objective of this clinical case study is aimed at providing a nursing care plan to restore the altered patterns in patients with acute lithiasic cholecystitis, providing care with quality, warmth and efficacy; making your hospital stay more comfortable